Design, Evaluation and Comparative Study of Pulsatile Releasefrom Tablet and Capsule Dosage Forms: Pulsatile release from tablet and capsule dosage forms - Monica Rao; Gajanan N. Parikh; Sameer Borate; Anuradha Ranpise; Yogesh Mandage; Kaushik Thanki (Iranian Journal of Pharmaceutical Sciences, 2009)
The objective of present research was to design, evaluate and compare drug release from two different dosage forms in pulsatile drug delivery system (DDS) for Metoprolol tartarate (MT) as tablet and capsule. Pulsatile systems are gaining a lot of interest as they deliver the drug at the right site of action at the right time and inthe right amount, thus providing spatial and temporal delivery and in creasingpatient compliance. These systems are designed according to the circadian rhythm of the body. The principle rationale for the use of pulsatile release is for the drugs where a constant drug release, i.e., a zero-order release is not desired. The release of the drug as a pulse after a lag time has to be designed in such a way that a complete and rapid drug release follows the lag time. Conclusively, the current study attained the successful comparison of drug release from two different pulsatile drug delivery systems.